Efficacy of insecticides in controlling pod borer (Helicoverpa armigera Hubner) infesting chickpea (Bangladesh Journal of Agricultural Research, 2017)
A field experiment was carried out at the Regional Pulses Research Station of Bangladesh Agricultural Research Institute, Madaripur, Bangladesh during rabi season of 2013-14 and 2014-15 to select effective insecticides to control pod borer (Helicoverpa armigera Hubner) of chickpea (Cicer arietinum). Signinificantly the highest insect infestation and yield loss were recorded from untreated control. Spray with every insecticide for 3 times at 7 days interval reduced insect infestation and yield loss significantly over control in both years. Reduction in insect infestation was 11.77-18.77% and 6.34-13.34% and yield loss was 280-393-168-281 kgha-1 in 2013-14 and 2014-15, respectively. The highest grain yield was obtained with Tracer 45 SC (Spinosad) (1177 kgha-1) followed by Volium Flexi 300 SC (Thiamethaxam) (1045 kgha-1) and Belt 24 WG (Flubendiamide) (1020 kgha-1) in first year. In second year, Tracer 45 SC produced maximum yield (1396 kgha-1) followed by Volium Flexi 300 SC (1315 kgha-1) and Admire 200 SL (Imidacloprid) (1300 kgha-1). In 2013-14, the highest benefit cost ratio (3.39) was obtained with Volium Flexi 300 SC followed by Belt 24 WG (2.65) and Admire 200 SL (1.67). In 2014-15, the highest benefit cost ratio was also obtained with Voilum Flexi 300 SC (2.38) followed by Admire 200 SL (1.79) and Belt 24 WG (1.63). Comparing two years data considering highest profit, Volium Flexi 300 SC might be applied @ 0.05% at an interval of 7 days to the crop for three times.Bangladesh J. Agril. Res. 42(2): 373-378, June 2017